Parallel Storage Devices Profiling with SeRRa - Machado, Vinicius; Boito, Francieli; Kassick, Rodrigo; Bez, Jean Luca; Navaux, Philippe; Denneulin, Yves (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2015: Anais do XIV Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2015)
This work presents the parallel storage device profiling tool SeRRa. Our tool obtains the sequential to random throughput ratio for reads and writes of different sizes on storage devices. In order to provide this information efficiently, SeRRa employs benchmarks to obtain the values for only a subset of the parameter space and estimates the remaining values through linear models. The MPI parallelization of SeRRa presented in this paper allows for faster profiling. Our results show that our parallel SeRRa provides profiles up to 8:7 times faster than the sequential implementation, up to 895 times faster than the originally required time (without SeRRa).